2006
DOI: 10.1088/1751-8113/40/3/010
|View full text |Cite
|
Sign up to set email alerts
|

A Bell inequality analog in quantum measure theory

Abstract: One obtains Bell's inequalities if one posits a hypothetical joint probability distribution, or measure, whose marginals yield the probabilities produced by the spin measurements in question. The existence of a joint measure is in turn equivalent to a certain causality condition known as "screening off". We show that if one assumes, more generally, a joint quantal measure, or "decoherence functional", one obtains instead an analogous inequality weaker by a factor of √ 2. The proof of this "Tsirel'son inequalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…In section 3 we show that there is a set of inequalities on the correlations that is implied by the existence of a strongly positive joint decoherence functional or quantal measure on the (fictitious) joint sample space of all possible outcomes of both of Alya's and both of Bai's experiments. This tightens the bounds derived in reference [2].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In section 3 we show that there is a set of inequalities on the correlations that is implied by the existence of a strongly positive joint decoherence functional or quantal measure on the (fictitious) joint sample space of all possible outcomes of both of Alya's and both of Bai's experiments. This tightens the bounds derived in reference [2].…”
Section: Introductionsupporting
confidence: 85%
“…Each PR box maximally violates one of the 8 CHSH inequalities. In [2] it was shown that the PR box admits a joint quantal measure, indeed a decoherence functional that does the job for one of the PR boxes is explicitly given in that paper. By doing the appropriate bit-flip on that decoherence functional (either flip the outcome of the a ′ measurement or swap b and b ′ : both produce the same result), we obtain the decoherence functional for the PR box (4.1): The remaining elements which are not equal to one of the above by Hermiticity are zero.…”
Section: Pr Boxesmentioning
confidence: 90%
See 1 more Smart Citation
“…Second, strong positivity is preserved under composition of subsystems, whereas the obvious "product measure" of two weakly positive quantal measures is not in general positive at all. And third -at a technical level -the histories hilbert space to which strong positivity leads has already proven to be useful in certain applications [22,23], while there are also indications that the map taking events α ∈ A to vectors in H could be of aid in the effort to extend the decoherence functional from A to a larger fragment of the σ-algebra it generates.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we will work in the framework of Quantum Measure Theory [24,17,8,11,25], which generalizes the mathematical concept of a measure-space so as to allow for quantal interference. When refashioned in this language, Quantum Mechanics appears as a generalized probability theory of a type inspired by the path integral.…”
Section: Introductionmentioning
confidence: 99%